Defining the meaning of independent living among persons with intellectual disabilities: a systematic literature review - Mohd Kamil, Nur Khaleeda; Amin, Aizan Sofia; Md Akhir, Noremy; Sutan, Rosnah; Ahmad Badayai, Abdul Rahman; Khairuddin, Khairul Farhah; Wan Abdullah, Wan Arnidawati; Mohd Zambri, Insyirah (Human Resource Management Academic Research Society, 2022)
Independent living is one movement that enables people with disabilities to exercise choice and control over their lives and make all decisions regarding their own lives. Article 19 of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) clearly stated that any person with disabilities deserves the same opportunity to make choices and control their life. Persons with disabilities may choose where and with whom they live on an equal basis with others and are not obliged to live in a particular living arrangement. Even though many studies discuss the concept of independent living among persons with disabilities in general, the research focusing on intellectual disability is still limited. Thus, this research aims to define the meaning of independent living among persons with intellectual disabilities. This systematic literature review adapts the publication standard of ROSES. It analysed 30 relevant articles from Scopus and Web of Science databases. The study identified three themes regarding the meaning of independent living among persons with intellectual disability, namely (a)responsibility, (b)decision making, and (c)new skills. Therefore, this paper discusses how the three themes emerged and the three central meanings of independent living for intellectual disabilities.